ToF-SIMS and AFM Characterization of Brown Cosmetic Contact Lenses: From Structural Analysis to the Identification of Pigments - Seon Hee Kim; Jihye Lee; Yun Jung Jang; Kang-Bong Lee; Yeonhee Lee (Journal of Analytical Methods in Chemistry)
Over the years, soft contact lenses for vision correction and cosmetic and therapeutic purposes have been greatly improved. For cosmetic contact lenses, the pigments need to be nontoxic, and the position of the pigment layer is particularly important because of the risks posed by pigment elution and the roughness of the lens surface. In this paper, we characterized the properties of brown cosmetic contact lenses made by three different manufacturers using surface analytical techniques. The surface topographies of the noncolored and colored parts were obtained by atomic force microscopy (AFM), and the position and composition of the pigment layer were determined by analyzing the cross section of the contact lenses using scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX). The influence of pigment location on surface roughness was also examined. In addition, to find the method of the evaluation for the risk of surface elution of the pigments in the colored parts, the mass spectra and ion images of the surfaces were obtained by time-of-flight secondary ion mass spectrometry (ToF-SIMS) with a new sample preparation. From the ToF-SIMS spectra, we observed specific fragment ions of the poly(hydroxyethyl methacrylate) (PHEMA) polymer and found differences in the composition of the pigment layer depending on the manufacturers. The cross-sectioned image and 3D chemical characterizations of metallic and specific ions in the brown cosmetic contact lenses clearly indicated the spatial distribution and location of the pigment layer that can be used for the evaluation of pigment elution.